Early Childhood Nature as the Basis for Developing Islamic Learning - Ayu Yunengsih; Gina Asri Hasnatunisa; Fuji Fauziah; Balebat Budiarti; Niah Nurhikmah (STIT Attaqwa, 2026)
This study aims to describe the concept of early childhood innate nature from an Islamic educational perspective and explain how innate nature can serve as a foundation for developing learning in early childhood education institutions. The study employed a literature review method, reviewing Islamic education books, works by classical and contemporary scholars, and relevant journal articles. Content analysis was conducted to identify the concepts, patterns, and implications of innate nature-based education. The results indicate that innate nature encompasses children's fundamental potentials, such as faith, reason, morality, play, and learning abilities, all of which require developmentally appropriate stimulation. Early childhood education that aligns with innate nature results in holistic child development, encompassing spiritual, cognitive, socio-emotional, and moral aspects. However, practice still demonstrates the dominance of early childhood academic learning that pays little attention to children's natural potential. This study emphasizes the importance of curriculum development, learning methods, and the role of early childhood teachers, who serve as educators in maintaining and developing innate nature. The conclusion of this study is that innate nature-based education is considered relevant for building children's character and intelligence in a balanced manner within the framework of Islamic values.